Expected Errors Arising from the Use of Artificial Intelligence in Concluding Contracts: "The Sale Contract" as a Model - Mansur, Ayah; Al Ahmad, Sohail (Ahliya Journal of Business Technology and MEAN Economies, 2025)
This study aims to analyze the expected errors arising from the use of artificial intelligence techniques in drafting and concluding contracts, focusing on the "Sale Contract" as a model, in light of rapid technological development and the legal and Sharia issues it raises regarding the accuracy and legitimacy of automated drafting. The originality of this study stems from addressing a contemporary topic that keeps pace with the digital transformation in civil and commercial transactions, and its attempt to build a jurisprudential and legal perception that regulates the use of AI and limits the risks of uncertainty (Gharar) and ignorance (Jahl). The study adopted a descriptive, analytical, and comparative approach to present concepts, analyze jurisprudential texts and Sharia evidence, and compare positions towards technical errors. The study reached a set of results, most notably that AI is an effective auxiliary tool for accelerating procedures, but it does not possess legal capacity to contract and cannot be fully relied upon without human review, as algorithmic and subjective errors may arise affecting the validity of the contract, with responsibility falling on the developer or user. Accordingly, the study recommended not fully relying on automatically generated contracts, enhancing human oversight and legal review, developing AI tools to increase transparency, establishing regulatory and ethical frameworks for its use in financial transactions, and training specialists to analyze the risks associated with AI outputs.